Spatial Distribution Of Diarrhea Cases In East Nusa Tenggara 2021-2023 - Nabila Wildan Naufa (CV. AFDIFAL MAJU BERKAH, 2026)
Diarrhea is a public health problem that remains a burden in Indonesia, including in East Nusa Tenggara (NTT) Province, with fluctuating incidence patterns every year. A spatial approach is needed to understand the distribution of cases and variations between regions. This study aims to map the spatial distribution of diarrhea cases and describe regional patterns based on population density and the percentage of open defecation (BABS) in East Nusa Tenggara Province in 2021–2023. This study is an ecological study with a cross-sectional approach using secondary data from the NTT Provincial Health Profile in 2021–2023. The unit of analysis is 22 districts/cities. The dependent variable is the number of diarrhea cases, while the independent variables include population density and the percentage of open defecation. Spatial distribution was carried out using QGIS version 3.28 through visualization of centroid maps and bivariate maps. The number of diarrhea cases in NTT during the 2021–2023 period showed a fluctuating pattern, with an increase in 2022 and a slight decrease in 2023. The distribution of cases was uneven across regions, with several districts such as East Sumba and South Central Timor showing high numbers of cases. Bivariate mapping results showed no consistent pattern between population density, the percentage of open defecation, and the number of diarrhea cases. The distribution of diarrhea cases in NTT showed a pattern that varied across regions and was not always in line with population density or the percentage of open defecation. This indicates that the incidence of diarrhea is multifactorial and influenced by various other factors at the regional level.